Implementation of Islamic Religious Education in the Fullday School Model in Forming Student Character and Discipline in SD ‘Aisyiyah 1 Mataram - Mardiyah Hayati; Mappanyompa Mappanyompa (Proceedings of The ICECRS, 2020)
The purpose of this research is to know how to implement Islamic education on the Model Full Day School in forming character and discipline of students in elementary school ' Aisyiyah 1 Mataram, learning process, constraints and solutions. This research is a field research conducted at Aisyiyah 1 Mataram Elementary School. ' Aisyiyah Elementary School 1 Mataram is the first elementary school established by the regional administrator of ' Aisyiyah West Nusa Tenggara. The kind of approach used is qualitative that generates descriptive data in the form of written or spoken words from those observed. The methods used in this study are: (1) Interviews, this method is used to obtain data on the material, strategies and models of the learning of Al-Islam in the ABA KINDERGARTEN. (2) Observation, this method is to see directly related to the learning process of Al Islam and Kemuhammadiyahan in ABA TK. (3) Documentation, this method to obtain data about the overview of the school, the history of the establishment, the state of teachers and students. (4) Data analysis. In analyzing the researcher's data using qualitative diskriptif.